Analysis of critical drivers affecting implementation of agent technology in a manufacturing system - Om Ji Shukla; Abhijeet Joshi; Gunjan Soni; Rajesh Kumar (Journal of Industrial Engineering International, 2019)
Technological advancement in the manufacturing system in current scenario is inevitable due to today's customer-driven and volatile nature of the market. Implementation of agent technology in a manufacturing system increases flexibility which handles uncertainty generated due to advance technology. Therefore, in this paper, the critical drivers affecting implementation of agent technology are identified and the relationships among them are analysed for a case study of a manufacturing system in an Indian steering wheel manufacturing company. Interpretive structural modelling (ISM) is used to provide binary relationships among identified critical drivers (CDs), while MICMAC approach describes sensitive analysis of driving and dependence behaviour of CDs. The classification of the drivers affecting agent technology and their relationships according to ISM-MICMAC approach provides importance to this study. A structural model is developed for providing rank to the identified critical drivers, and driving-dependent power diagram is presented for analysing the behaviour of different critical drivers with respect to others. The identification of the most influential CDs that lead to increase the effect of other drivers is the major finding of this study. Finally, the implication of this research for the industries is also described.
Keywords: 650; Agent technology (AT); Interpretive structural modelling (ISM); Manufacturing system; Critical drivers (CDs); MICMAC analysis